Neuroimaging evidence of deficient axon myelination in Wolfram syndrome - Lugar, Heather M. (Nature Publishing Group, 2016)
Wolfram syndrome is a rare autosomal recessive genetic disease characterized by insulin dependent diabetes and vision, hearing and brain abnormalities which generally emerge in childhood. Mutations in the WFS1 gene predispose cells to endoplasmic reticulum stress-mediated apoptosis and may induce myelin degradation in neuronal cell models. However, in vivo evidence of this phenomenon in humans is lacking. White matter microstructure and regional volumes were measured using magnetic resonance imaging in children and young adults with Wolfram syndrome (n = 21) and healthy and diabetic controls (n = 50). Wolfram patients had lower fractional anisotropy and higher radial diffusivity in major white matter tracts and lower volume in the basilar (ventral) pons, cerebellar white matter and visual cortex. Correlations were found between key brain findings and overall neurological symptoms. This pattern of findings suggests that reduction in myelin is a primary neuropathological feature of Wolfram syndrome. Endoplasmic reticulum stress-related dysfunction in Wolfram syndrome may interact with the development of myelin or promote degeneration of myelin during the progression of the disease. These measures may provide objective indices of Wolfram syndrome pathophysiology that will be useful in unraveling the underlying mechanisms and in testing the impact of treatments on the brain.